Joint Board-Management Meetings and Firm Performance - Dian Agustia; Iman Harymawan; John Nowland (Australasian Accounting, Business and Finance Journal, 2022)
Are joint meetings between boards of directors and top management teams associated with better decision making or higher agency costs? We examine formally scheduled joint board-management meetings as a channel for closer interaction between boards of directors and top management teams. Using publicly disclosed data from Indonesian firms, we find that about half of our sample firms hold joint board-management meetings and more meetings are associated with higher firm performance. This suggests that the benefits from information sharing at joint meetings are greater than the agency costs. This relationship is most significant when companies hold 10-12 joint board-management meetings per year, in companies with good governance and when companies are experiencing poor performance. For policymakers and practitioners, we highlight a formal channel for closer interaction between directors and management that benefits shareholders.
Keywords: Board of directors; Corporate governance; Firm performance; Meetings; Top management team